Child Support Right In The Human Rights Perspective - Alam, Arief Syahrul; Chaidar, Muhamad; Ngah, Anisah Che (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The provision of Article 28 B paragraph (2) and Article 28 D paragraph (1) of the 1945 Constitution of the Republic of Indonesia can be stated as the philosophical basis for children's rights on viability, growth, and development; and the rights to protection from violence and discrimination; as well as the rights to recognition, assurance, fair legal protection, and certainty, as well as equal treatment in front of the law.Purposes of the Research: To find out that every regulation related to child support rights from the human rights perspective should refer to the philosophical basis of the nation that is Article 28 B paragraph (2) and Article 28D paragraph (1) of the 1945 Constitution of Republic of Indonesia. The focus of the legal problem in this study is child support rights from the human rights perspective.Methods of the Research: The juridical normative method with statute approach, conceptual approach, constitutional approach, and Comparative approach is used as the research methodology in this study.Results of the Research: However, with the implementation of Article 28 B paragraph (2) of the 1945 Constitution of Republic of Indonesia that placed the State, Government, and Regional Governments are obliged to ensure the protection, care, and welfare of the children by paying attention to the rights and obligations of the parents, guardians or other people who legally responsible to the children. The provision of that Article asserts that the problem of children's protection is not only the responsibility of their parents, but also has become the responsibility of the state, government, and regional government. Therefore, it can be concluded that the post-divorce child maintenance rulings in Malaysia are better than those in Indonesia, as the implementation of child maintenance rulings in Malaysia is monitored by the BSK, which is a part of the Court responsible for handling all matters related to child support.